1992
DOI: 10.1002/jnr.490330413
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol prevents induction of the hsp70 heat shock gene in neurons injured by phencyclidine (PCP), MK801, and ketamine

Abstract: The non-competitive NMDA receptor antagonists, PCP (phencyclidine), MK801, and ketamine produce psychosis in humans and abnormal vacuoles in posterior cingulate and retrosplenial rat cortical neurons. We show that PCP (> or = 5 mg/kg), MK801 (> or = 0.1 mg/kg), and ketamine (> 20 mg/kg) induce hsp70 mRNA and HSP70 heat shock protein in these vacuolated, injured neurons, and PCP also induces hsp70 in injured neocortical, piriform, and amygdala neurons. The PCP, MK801, and ketamine drug induced injury occurs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 87 publications
4
57
0
Order By: Relevance
“…Interestingly, the same authors and others reported that chronic PCP treatment over 3-14 days causes irreversible necrotic toxicity and apoptosis that spreads to many corticolimbic brain regions (eg the amygdala, dentate gyrus, entorhinal cortex, olfactory tubercle, and piriform cortex; Ellison and Switzer, 1993;Ellison, 1994;Corso et al, 1997;Johnson et al, 1998;Phillips et al, 2001;Sharp et al, 2001). These effects of PCP are blocked by antipsychotic drugs (Sharp et al, 1992;Johnson et al, 1998;Olney et al, 1999). No changes in absolute serotonin or dopamine concentrations have been reported with either acute or chronic treatment using high doses of PCP suggesting that there are no neurochemical lesions of these two important neurotransmitter innervations likely to be involved in the rewarding/ dysphoric actions of PCP (Jentsch et al, 1997b;Noda et al, 2000;Balla et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the same authors and others reported that chronic PCP treatment over 3-14 days causes irreversible necrotic toxicity and apoptosis that spreads to many corticolimbic brain regions (eg the amygdala, dentate gyrus, entorhinal cortex, olfactory tubercle, and piriform cortex; Ellison and Switzer, 1993;Ellison, 1994;Corso et al, 1997;Johnson et al, 1998;Phillips et al, 2001;Sharp et al, 2001). These effects of PCP are blocked by antipsychotic drugs (Sharp et al, 1992;Johnson et al, 1998;Olney et al, 1999). No changes in absolute serotonin or dopamine concentrations have been reported with either acute or chronic treatment using high doses of PCP suggesting that there are no neurochemical lesions of these two important neurotransmitter innervations likely to be involved in the rewarding/ dysphoric actions of PCP (Jentsch et al, 1997b;Noda et al, 2000;Balla et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…This proposal was supported by findings showing that antipsychotic drugs blocked the limbic cortical injury in rodents produced by PCP, ketamine, and MK-801 (Farber et al, 1993;Olney and Farber, 1994;Sharp et al, 1992). Haloperidol blocked the injury to retrosplenial cortex produced by NMDA-receptor antagonists in rats (Sharp et al, 1992(Sharp et al, , 1993(Sharp et al, , 1994a.…”
Section: Introductionmentioning
confidence: 91%
“…It has been demonstrated in injured, vacuolated neurons and Hsp70 immunostaining has been used as a marker for neuronal injury following administration of MK-801, ketamine and phencyclidine (PCP) (Olney et al, 1991;Sharp et al, 1991Sharp et al, , 1992Sharp et al, , 1994aNakki et al, 1995Nakki et al, , 1996Rajdev et al, 1998;Tomitaka et al, 2000a, b). Hsp70 protein is induced by the presence of denatured proteins in cells and is generally induced in cells that will survive an injury (Sharp et al, 1999).…”
Section: Hsp70 Immunocytochemical Assessment Of Neuronal Injurymentioning
confidence: 99%
See 2 more Smart Citations